Pengaruh Model Diskursus Multi Representasi (DMR) Terhadap Kemampuan Menulis Teks Negosiasi Siswa Kelas X SMA N 1 Batang Kuis Tahun Pembelajaran 2022/2023 - Putri Ardiani Lubis (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to determine the effect of the Model Discourse Multi Representation (DMR) on the ability to write negotiating texts for class X students of SMA N 1 Batang Kuis in the 2022/2023 Academic Year. This study used an experimental method to see the effect of a treatment on students' ability to write negotiating texts using the Discourse Multi Representation (DMR) model. The population in this study were all students of class X consisting of 9 classes totaling 324 students. The sample of this research is class X MIA-1 totaling 36 students and X MIA-2 totaling 36 students with purposive sampling technique. The research design used was a two group posttest design with an essay test instrument. Based on the data processing carried out, the average value of the experimental class with the Discourse Multi Representation (DMR) model = 86.33, a standard deviation of 7.079, while the average value of the control class with the conventional model (lecture) = 73.86, a standard deviation 6,94. Based on the normality test carried out on the post-test results of the experimental class and the control class, it is known that the distribution is normal. Based on the post test homogeneity test it was stated that the samples of the two variables came from homogeneous populations. After the normality test and homogeneity test is carried out, it is known that Tcount = 7.55 After Tcount is known, then this value will be consulted with the t table at a significance level of 5% or 0.05 with df=n-1, df=36-1=35 obtained significance level of 5% is 1.689. Because the Tcount obtained is greater than Ttable, namely 7.55 > 1.689, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that the Discourse Multi Representation model has an effect on the ability to write negotiating texts for class X SMA N 1 Batang Kuis  in the 2022/2023 Academic Year. Keywords: Influence, Model Discourse Multi Representation (DMR), Writing Negotiation Text.